Overcoming Fundamentalism: Ethical Responses from Five Continents - Kochuthara, Shaji George (Asian Horizons, 2010)
Heidi Hadsell and Christoph Stückelberger, ed., Overcoming Fundamentalism: Ethical Responses from Five Continents, Geneva: Globethics.net, 2009. Pages: 212. ISBN: 978-2-940428-00-7.